2014
DOI: 10.1007/s10964-014-0156-1
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Adolescents’ Sleep Patterns: Contextual Correlates and Implications for Health and Adjustment in Young Adulthood

Abstract: Late adolescence is a period of substantial risk for unhealthy sleep patterns. This study investigated the contextual correlates and health and adjustment implications of sleep patterns among Mexican American youth (N = 246; 51% female). We focused on Mexican American youth because they represent a large and rapidly increasing subgroup of the U.S. population that is at higher risk for health and adjustment problems; this higher risk may be explained, in part, by sleep patterns. Using data from 7 phone diary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Studies have not found an association between parent education level and children’s onset IIV [37,40] or duration IIV when controlling for other important demographic/environmental variables such as age and parent income [37,40]. Among studies that used a composite measure of SES, one did not report an association with duration IIV when the composite included family income and parent education measured five years prior to the sleep assessment [48]. In contrast, two other studies using more indicators to assess SES found lower SES to be associated with greater onset IIV and greater duration IIV [34,49].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have not found an association between parent education level and children’s onset IIV [37,40] or duration IIV when controlling for other important demographic/environmental variables such as age and parent income [37,40]. Among studies that used a composite measure of SES, one did not report an association with duration IIV when the composite included family income and parent education measured five years prior to the sleep assessment [48]. In contrast, two other studies using more indicators to assess SES found lower SES to be associated with greater onset IIV and greater duration IIV [34,49].…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis was largely supported and results were remarkably consistent across the two samples, pointing to the importance of positive parenting behaviors for promoting sleep behaviors and in turn reducing risk for engaging in problematic behaviors. Using a phone diary interview methodology, Kuo et al (2015) examined the family context (in addition to school, work, and peer contexts) in a sample of 246 Mexican-American adolescents. The authors found that more time spent working, at school, or with peers was associated with obtaining less sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%
“…Increasing research shows that insufficient sleep and irregular sleep patterns have a negative impact on psychological (Barnes & Meldrum, 2015) and physical health (Kuo et al, 2015) as well as academic outcomes (Asarnow, McGlinchey & Harvey, 2014). Biobehavioral perspectives on sleep posit that environmental threat and psychosocial stressors heighten vigilance and alertness, which are antithetical to restful sleep (Dahl & Lewin, 2002).…”
Section: Introductionmentioning
confidence: 99%